An analysis of the determinants of job search effort - Ng, Jia Wen (2013)
To more wholly engage the workforce is to be able to attract, motivate and retain employees. This study focused on 5 factors influencing job search effort: learning goal orientation, calling, career aspirations, job search self-efficacy and employment commitment. A longitudinal study was conducted on a cohort of 1084 accountancy and business graduating job seekers. Of the 1084 job seekers, 245 of them completed both the Time 1 survey, which measured learning goal orientation, job search self-efficacy and employment commitment and the Time 2 survey, which measured the job search effort of the individuals. Through this study, we found that learning goal orientation, calling, leadership, job search self-efficacy and employment commitment had a positive relationship with job search effort. Of the 5 factors, job search self-efficacy had the largest influence on the variance of job search effort. Our study on graduating job seekers hopes to bring about a better understanding of what attracts potential talents so that organizations can better utilize their recruitment funds.